Bridging realms: Western client perspectives on psychotherapy inspired by Indigenous healing - Trnka, Radek; Krtek, Arnost; Lorencova, Radmila (Explore (New York, N.Y.), 2024)
CONTEXT: The decolonial turn in psychology criticizes conventional Western psychotherapeutic frameworks and seeks to decolonize therapeutic practices by considering diverse cultural perspectives. Indigenous healing has been increasingly used in the psychotherapy of ethnic communities, but also in the psychotherapy of Western clients. The research questions of the present study were focused on how Western clients experience the therapies inspired by Indigenous healing. OBJECTIVE: The study aimed to explore the motivations, experiences, and mental health outcomes of participants of therapies inspired by Indigenous healing with a focus on issues related to intercultural transfer of therapeutic practice. DESIGN: Semi-structured qualitative interviews were used to gather narratives from 28 participants. Thematic analysis was used for data analysis. RESULTS: Participants reported the following long-lasting outcomes of Indigenous therapies: increased well-being, calm, satisfaction with life, better emotion regulation, coping with stress, behavioral control, problem solving, decision making as well as a more sensitive and deeper experience of reality. Conventional Western psychotherapy was perceived as conversation-based, while Indigenous therapy was perceived as experience-based and more complex. The integration of experiences from Indigenous therapies was more difficult in the Western sociocultural environment compared to participation in the place of their origin, within the community of Indigenous people. CONCLUSION: Indigenous healing has beneficial outcomes for Western clients, but the integration of these experiences is quite difficult and requires systematic psychotherapeutic support in the Western cultural environment.
Keywords: psychoterapie; Adaptation, Psychological; Male; Psychotherapy; Mental Health; Adult; dospělí; duševní zdraví; mužské pohlaví; adaptace psychologická; tradiční lékařství; kvalitativní výzkum; lidé; Cultural context; ženské pohlaví; Humans; Medicine, Traditional; Mental health; Indigenous healing; Qualitative Research; Female; lidé středního věku; Middle Aged